Dry Eyes Syndrome pada Penderita Diabetes Melitus Tipe 2 - Setyorini, Desti Putri; Wildan, Arief; Nugroho, Trilaksana; Julianti, Hari Peni; HS, Heri-Nugroho (Medica Hospitalia : Journal of Clinical Medicine, 2021)
BACKGROUND : Type 2 diabetes mellitus patients have risk to suffer from dry eyes syndrome (DES), caused by peripheral and autonomic neuropathy, oxidative stress, and metabolic dysfunction. DES can reduce the patient’s quality of life then it could induce blindness if the patient didn’t get any therapy for DES. It is important to prevent DES by controlling its risk factors. OBJECTIVE : To investigate risk factors of DES in patients with type 2 diabetes mellitus. METHOD : . This study was an analytical observational study with cross-sectional design and purposive sampling. Subjects were examined by using questionnaire and slit lamp, then followed by deep interview in some subjects. This study was also using subject’s medical record to complete the required data. Subjects were diagnosed to suffer DES if OSDI score >12 and schirmer score <10mm. Data was analyzed by using statistic software. RESULT : . From 42 subjects, 19 subjects (45,2%) suffered from DES whereas another 23 subjects (54,8%) didn’t. There was significant relation between diabetic retinopathy (p=0.009) and DES in patients with type 2 diabetes mellitus showed by p value under 0,05 (OR 5.700, 95% CI:1.364-23.821). However, age (p=0.516), gender (p=1.000), level of knowledge (p=0.555), accessibility to health provider (p=1.000), occupation (p=0.644), economic level (p=0.105), smoke exposure (p=0.432), duration of diabetic (p=0.707), diabetic controlling (p=0.305), and history of dyslipidemia (p=0.155) had no significant relations with DES in patients with type 2 diabetes mellitus. CONCLUSION : There is a significant relation between diabetic retinopathy and DES in patients with type 2 diabetes mellitus. Diabetic retinopathy is the most dominant risk factor among the other factors in this study.